Analysis of quality control on cassava emping “Super Telur Bu Siti” in Bantul Karang Yogyakarta - Timur, Farradila Caesar Ratna; Fitriani, Aprilia (Journal of Halal Science and Research, 2024)
Cassava emping is a snack made from mashed cassava mixed with eggs, red chilies, green onions, and celery leaves. This research aims to analyze the quality control of cassava emping products and efforts to improve the production process of "Super Telur Bu Siti" Cassava Emping. Data collection methods in this research are interviews, observation, and literature study. Several problems are caused by facts that need to conform to standards in similar food production processes. From the analysis using affinity diagrams, several factors cause quality problems, namely materials, machines, methods, humans, and the environment. The alternative tree diagram analysis results are efforts or actions to improve the quality of cassava chip products in "Super Telur Bu Siti" Cassava Emping. This research concludes that quality control is carried out based on aspects of raw materials, processes during processing, and final products. The Cassava Emping product "Super Telur Bu Siti" does not meet the quality standard criteria based on the National Standards and the Indonesian Food and Drug Supervisory Agency regarding Good Food Production Methods for Home Industries or CPPB-IRT 2012.